Lana Del Reys Off to the Races and Its Allusions to Vladimir Nabokovs Lolita - Sindhy Sintya Mianani (Journal of Language and Literature, 2019)
No matter the era, ones always relate to the popular media whether it is literary words, song lyrics or movies. Yet, sometimes ones do not recognize the reference from a particular textual discourse swirling around them. From this premise, Lana Del Reys Off to the Races is deemed as the perfect example of this issue. Lana Del Reys Off to the Races is an intriguing song, for its lyrics are said to have some relations to Vladimir Nabokovs Lolita. For her adaptation on Nabokovs Lolita, Del Rey has been attacked for ostensible discrepancies on who Lolita really is. Thus, this study attempts to prove the relation between Lana Del Reys Off to the Races to Vladimir Nabokovs Lolita through Julia Kristevas theoretical ideas on intertextuality. The discussion of this study indicates that, indeed, there is a relation between Lana Del Reys Off to the Races to Vladimir Nabokovs Lolita. The lyrics of Off to the Races contains several lines and phrases indicating that Vladimir Nabokovs Lolita plays important role in its meanings. However, the some adaptations and reversal of the relationship between Lolita and Humbert in Off to the Races brings an entirely altered meaning to the song than the meaning in the original text.Keywords: intertextuality, lyrics, Lolita.